Dalagang bukid - Garcia, Florendo R.; Ignacio, Leon.; Ilagan, Hermogenes; Padilla, Monon; Roxas, Teresa Escoda; Tiongson, Nicanor; Cultural Center of the Philippines (Manila The Center, 1987)
Tanghalang Pilipino & production of Hermogenes Ilagan and Leon Ignacio's zarzuela entitled Dalagang Bukid with Noemi Manikan-Gomez as Angelita. This is also a tribute to Atang de la Rama who is the lead character in this zarzuela which was staged in 1919.
VHS.
Noemi Manikan-Gomez; Cynthia Patag; Pablo Molina; Lou Veloso; Gamaliel Viray.
Musical direction, Andrea O. Veneracion; choreography, Edna Vida.
Keywords: Zarzuela